A cell-penetrating peptide enhances delivery and efficacy of phosphorodiamidate morpholino oligomers in mdx mice - Li Gan; Leslie C.L. Wu; Jenna A. Wood; Monica Yao; Chris M. Treleaven; Nelsa L. Estrella; Bruce M. Wentworth; Gunnar J. Hanson; Marco A. Passini (Elsevier, 2022)
Antisense RNA technology is a strategy for the treatment of Duchenne muscular dystrophy (DMD), a progressive and universally fatal X-linked neuromuscular disease caused by frameshift mutations in the gene encoding dystrophin. Phosphorodiamidate morpholino oligomers (PMOs) are an antisense RNA platform that is used clinically in patients with DMD to facilitate exon skipping and production of an internally truncated, yet functional, dystrophin protein. Peptide-conjugated PMOs (PPMOs) are a next-generation platform in which a cell-penetrating peptide is conjugated to the PMO backbone, with the goal of increasing cellular uptake. RC-1001 is a PPMO that contains a proprietary cell-penetrating peptide and targets the Dmd mutation in mdx mice. It was evaluated in mdx mice for exon 23 skipping, dystrophin production, and functional efficacy. Single-dose RC-1001 dose dependently increased exon skipping and dystrophin protein levels in striated muscle and is associated with improvements in muscle function. Dystrophin protein levels were durable for 60 days. Three doses, each given 1 month apart, increased exon skipping to 99% in quadriceps and 43% in heart, with dystrophin protein levels at 39% and 9% of wild type, respectively. These findings support clinical development of PPMO therapies for the treatment of DMD.